STUDENTS’ SELF EFFICACY IN SPEAKING ENGLISH - Desma Ayuni Lestari; Melda Yeni; Sri Erma Purwanti (Program Studi Pendidikan Bahasa Inggris, 2020)
The purpose of this research is to determine how students' self-efficacy in speaking English at the second grade of computer and network engineering in SMKN 01 Kempas. This research is categorized as descriptive research. It was done at second grade of computer and network engineering, consisting of 30 students, 17 male, and 13 female. The instrument used was a questionnaire. After the data collected, the results obtained are the percentage of students' self-efficacy in speaking English from 37.50% to 67.85% of students studied online due to the corona pandemic, only 21 students participated in answering the questionnaire. one student has a low category,13 student have a medium category, and three student have a good category.